2015
DOI: 10.1021/acs.macromol.5b00733
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Entangled Linear Supramolecular Chains with Sticky Side Groups: Influence of Hindered Fluctuations

Abstract: The design and effective application of supramolecular transient polymer networks based on the assembly of entangled polymer building blocks requires not only precise description of relaxation mechanisms of the chain segments but also inclusion of the kinetics of reversible formation and breakage of reversible supramolecular interactions. In this work we extend the tube-based time marching algorithm to the entangled associative polymers with sticky side groups, with special emphasis on the effect of hindered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(145 citation statements)
references
References 62 publications
5
140
0
Order By: Relevance
“…As an addendum to the preceding argument based on primary polydispersity of the precursor‐polymer length and substitution, several previous studies have found evidence for cluster formation within supramolecular polymer networks, typically caused by secondary interactions between the supramolecular crosslinking motifs . Such clusters are likely to be another or additional cause for complex relaxation of these systems . For the present discussion, however, note that even the crosslinking motif with the strongest effect on relaxation of the polydisperse pNIPAAm‐based system, terpyridine (see Figures (III) and H), has been demonstrated to cause just little polymer‐network heterogeneity in the comparative regular star‐pEG‐based systems, which indeed all exhibit monoexponential long‐term relaxation.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…As an addendum to the preceding argument based on primary polydispersity of the precursor‐polymer length and substitution, several previous studies have found evidence for cluster formation within supramolecular polymer networks, typically caused by secondary interactions between the supramolecular crosslinking motifs . Such clusters are likely to be another or additional cause for complex relaxation of these systems . For the present discussion, however, note that even the crosslinking motif with the strongest effect on relaxation of the polydisperse pNIPAAm‐based system, terpyridine (see Figures (III) and H), has been demonstrated to cause just little polymer‐network heterogeneity in the comparative regular star‐pEG‐based systems, which indeed all exhibit monoexponential long‐term relaxation.…”
Section: Resultsmentioning
confidence: 63%
“…Both can be rationalized on basis of the following argument: transient interchain sticking contributes to the elastic part of the shear modulus of a supramolecular polymer network. On long timescales, flow is possible, but it is impaired by the interchain sticking . On a molecular scale, overcoming the sticking during flow requires supramolecular complex dissociation, and hence, input of the energy of activation for it, E a,sticker‐diss which closely matches the negative enthalpy of complex association, –Δ H sticking .…”
Section: Resultsmentioning
confidence: 99%
“…Several theoretical models have been proposed to describe the rheological response of telechelic polymers [77,78] and unentangled [41,[79][80][81][82] or entangled [83][84][85][86][87] supramolecular polymers. For unentangled polymers with supramolecular side-groups, the polymer type relevant to our work, the so-called sticky-Rouse model has been proposed [41,[79][80][81][82].…”
Section: Introductionmentioning
confidence: 99%
“…We estimated numerically J(t) from G*(x) using eqs (1)(2)(3)(4). The dashed lines in Figure 6 represent the estimated values based on the dynamic data.…”
Section: Creep Measurements For the Hg Polymermentioning
confidence: 99%
“…This method roughly can be categorized into two classes. One is the polymeric system with associations induced by hydrogen bonds, metal coordination, ion complexation, and so on. The other is the thermoplastic elastomer, which consists of hard associating segments and soft rubbery segments.…”
Section: Introductionmentioning
confidence: 99%